Hubungan Asupan Lemak dan Zat Besi dengan Kejadian Anemia Saat Menstruasi Pada Mahasiswa Di Asrama Kebidanan UNW Ungaran - Sri Wahyuni; Sang Ayu Kompiang Mira Arum Sari; Dyah Karunia Rahmawati (Universitas Ngudi Waluyo, 2019)
Blood loss during menstruation means removing the iron in the blood. Female adolescent have menstruation every month, so they need twice iron than men. Fat and Iron intake greatly affect the nutrition. One of the factors causing anemia in female adolescent is low levels of Hb in the blood during menstruation. This research aim to know the correlation of fat and iron intake with anemia during menstruation on students at midwifery dormitory of NgudiWaluyo University. The design of this study was correlational research, with cross sectional approach. The population was all of female students at Midwifery dormitory as many as 171 students. The technique used Quota Sampling of 63 students. The measurement tool used the examination of Hb levels by using digital Hb and quesioner. Statistic test used Kolmogorov-smirnov. most of students have anemia as many as as 66,6%(42 respondents, fat intake mostly included a severe deficit of 79.4% (50 respondents), while the highest iron intake in the severe deficit category was 36.5% (23 respondents). The test results of the correlation between fat Intake with anemia were found to be P = 0.139 and test of the correlation between Iron intake with the incidence of anemia was obtained P = 1,000. Intake of fat and iron intake has no correlation with the incidence of anemia